1999
DOI: 10.1177/002215549904700605
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and Cell Distribution of the Multidrug Resistance-Associated Protein (MRP) in Mouse Intestine and Kidney

Abstract: SUMMARYThe multidrug resistance-associated protein (MRP) that is involved in drug resistance and the export of glutathione-conjugated substrates may not have the same epithelial cell membrane distribution as the P-glycoprotein encoded by the MDR gene. Because intestinal and kidney epithelial cells are polarized cells endowed distinct secreting and absorptive ion and protein transport capacities, we investigated the tissue and cell distribution of MRP in adult mouse small intestine, colon, and kidney by immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 37 publications
10
95
1
Order By: Relevance
“…4A). Peng et al reported that Mrp1 is highly expressed in proliferative cells of crypts in mouse small intestine (17), and this was supported by the immunohistochemical analysis performed in the present study (Fig. 4C).…”
Section: Although Transporter(s) Expressed In Differentiated Epithelisupporting
confidence: 90%
See 2 more Smart Citations
“…4A). Peng et al reported that Mrp1 is highly expressed in proliferative cells of crypts in mouse small intestine (17), and this was supported by the immunohistochemical analysis performed in the present study (Fig. 4C).…”
Section: Although Transporter(s) Expressed In Differentiated Epithelisupporting
confidence: 90%
“…We focused on the localization of Mrp1 in proliferative cells in the small intestine (17), since MTX accumulation in such cells may be responsible for the severe intestinal toxicity observed in mrp1 (-/-) mice. In order to examine this possibility, the architecture of the small intestinal villi and the proliferation of the intestinal cells were investigated.…”
Section: Histological Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugiyama and co-workers have shown MRP2 to be functionally expressed in Caco-2 and rodent intestine, transporting organic anions and glutathione conjugates in a blood-tolumen direction (Gotoh et al, 2000;Hirohashi et al, 2000). MRP1 and MRP3 are also expressed in intestinal cells although the functional signi®cance of these transporters remains to be determined (Peng et al, 1999;Ortiz et al, 1999;Hirohashi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…MRP type transporters, studied primarily in over-expressing cell models, have the capacity to transport many substances including common drugs, often following enzymatic conjugation with glutathione, glucuronide or sulphate, although some MRPs may also act as unconjugated drug/glutathione co-transpor-ters Borst et al, 2000). Several members of the MRP family have been identi®ed at the molecular level in intestinal tissues (Mottino et al, 2000;Peng et al, 1999;Gotoh et al, 2000) and there is evidence that at least one of these, MRP2, is functionally active in this tissue (Gotoh et al, 2000). However, their contribution to intestinal drug e ux remains poorly de®ned.…”
Section: Introductionmentioning
confidence: 99%